THE CORRELATION BETWEEN LEARNING STYLES AND BIOLOGY LEARNING PERFORMANCE OF NIGERIAN STUDENTS - Abidoye, Florence Omosholape; Olorundare, Adekunle Solomon (JPBI (Jurnal Pendidikan Biologi Indonesia), 2020)
Learning style has been considered as one of determining factors for learning processes. This study aimed at observing the correlation between students? learning style and performance of Nigerian students in biology. The sample of this study consisted of 100 students which were randomly selected from the secondary schools in Ifelodun LGA, Kwara State, Nigeria. The two validated instrument used for data collection were Grasha & Reichmann?s Student Learning Scale and VAK/VARK Learning Style. The data gained were analyzed using percentage, Pearson correlation, and Chi-Square test. The study findings indicated that: (i) there was a negative correlation between students? academic performance and visual (-0.061) and kinesthetic learning style (-0.50), as well as positive correlation between the performance and auditory learning style (0.108). (ii) There were no significant differences between the study of learning styles, either visual (t(99) = 1.60, p = 0.11), auditory (t(99) = 1.33, p = 0.18), or kinesthetic (t(99) = 0.59, p = 0.55), of male and female biology students? performance. Thus, it is suggested that teachers choose the most proper learning methods which accommodate the students? need based on their learning styles.